2016
DOI: 10.3171/2015.2.jns142587
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural alterations in trigeminal neuralgia determined by diffusion tensor imaging are independent of symptom duration, severity, and type of neurovascular conflict

Abstract: T rigeminal neuralgia (TN) is characterized by recurrent episodes of intense and lancinating pain localized to the sensory supply areas of the fifth cranial nerve (CN V), which is also known as the trigeminal nerve. 11 The most frequent cause of TN is mechanical irritation of the nerve within a vulnerable zone that extents for about 4 to 5 mm from the point of transition from the peripheral (derived from Schwann cells) to the central myelin (derived from the oligodendroglia) (i.e., transition zone) to the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
46
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 37 publications
2
46
0
2
Order By: Relevance
“…Other three studies did not find differences in ADC values between affected and unaffected sides of patients and controls [13,24,25]. Concerning only DTI studies about TN caused by NVC, six articles found a significant decrease in FA values [14,17,[22][23][24][25] and two a significant increase in ADC values [17,23] in the affected nerves.The measurement of FA and ADC provides robust values for quantifying the degree of microstructural abnormalities of TGN. Degeneration or damage of white matter tracts is expected to result in reduced FA, owing to the loss of directionality of diffusion and increase in ADC, that is due to diffusivity being averaged in all spatial directions as a result of the loss of myelin and axonal membranes [1].…”
mentioning
confidence: 90%
See 3 more Smart Citations
“…Other three studies did not find differences in ADC values between affected and unaffected sides of patients and controls [13,24,25]. Concerning only DTI studies about TN caused by NVC, six articles found a significant decrease in FA values [14,17,[22][23][24][25] and two a significant increase in ADC values [17,23] in the affected nerves.The measurement of FA and ADC provides robust values for quantifying the degree of microstructural abnormalities of TGN. Degeneration or damage of white matter tracts is expected to result in reduced FA, owing to the loss of directionality of diffusion and increase in ADC, that is due to diffusivity being averaged in all spatial directions as a result of the loss of myelin and axonal membranes [1].…”
mentioning
confidence: 90%
“…Chen et al, Leal et al, and Lummel et al reported a significant elevation in ADC values in the affected sides of patients [7,17,23]. Other three studies did not find differences in ADC values between affected and unaffected sides of patients and controls [13,24,25]. Concerning only DTI studies about TN caused by NVC, six articles found a significant decrease in FA values [14,17,[22][23][24][25] and two a significant increase in ADC values [17,23] in the affected nerves.The measurement of FA and ADC provides robust values for quantifying the degree of microstructural abnormalities of TGN.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…MRI was performed on a 3.0-T MRI scanner (Signa HDx; 3T GE Healthcare) using a standardized protocol. [21] Images were obtained using an 8-channel head coil with sensitivity encoding parallel processing capability, with the application of 64 non-collinear directions of diffusion gradients. The sequences and their parameters are summarized in Table 1.…”
Section: Mri Examination and Analysismentioning
confidence: 99%